Hubungan Usia Ibu, Riwayat Anemia, dan Kekurangan Energi Kronis (KEK) dengan Kejadian Stunting pada Baduta di Desa Puyung Kecamatan Jonggat Kabupaten Lombok Tengah - Al-Aluf, Widad; Arjita, I Putu Dedy; Mathar, M. Ashhabul Kahfi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Stunting is a development and advancement clutter in children. The point of this investigate is to decide the relationship between maternal age, history of frailty, Chronic Energy Deficiency (KEK) and the rate of hindering in Baduta in Puyung Town, Jonggat Area, Central Lombok Rule. The strategy utilized in this investigate is to utilize a quantitative inquire about plan with a sort of observational explanatory inquire about, which is investigate that tries to investigate how and why the marvel happens, with a cross-sectional investigate plan approach. The comes about of research using the chi-square test appear that there's a critical relationship between a history of iron deficiency and the rate of stunting, to be specific moms with a history of iron deficiency have a better hazard compared to moms without a history of frailty with a p-value of 0.003. The comes about of investigate utilizing the chi-square test appear that there's a noteworthy relationship between Chronic Vitality Insufficiency (KEK) and the frequency of stunting, to be specific moms with Persistent Vitality Lack (KEK) have the next chance when compared to moms who don't involvement Unremitting Vitality Lack (KEK) with values p-value 0.005.